STRATEGI PEMBELAJARAN THINK TALK WRITE UNTUK MENINGKATKANKEMAMPUAN PENALARAN MATEMATIS SISWA KELAS IX SMPN 1 NAN SABARIS TAHUN PELAJARAN 2018/2019 - Isma Suci Muharni (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical reasoning is one of the abilities that must be developed by students in learning mathematics. But in the reality in class IX SMPN 1 Nan Sabaris the mathematical reasoning of students is still low. This is because the less facilitated student learning to develop thinking patterns. One of the way that can increase the students ability of mathematical reasoning is by applying Think, Talk, Write strategy in the mathematics learning. This research is a quasi experimental design with Static Group Design.The results showed that students who learn mathematical reasoning using Think, Talk, Write strategybetter than students who studied using conventional learning.Keywords – Matematical Reasoning, Strategi Think, Talk, Write